2023
DOI: 10.3389/fenvs.2022.1092196
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A dynamic relationship between renewable energy consumption, non-renewable energy consumption, economic growth and CO2 emissions: Evidence from Asian emerging economies

Abstract: This study aims to explore the relationship between renewable energy consumption, non-renewable energy consumption, carbon dioxide emissions and economic growth in China, India, Bangladesh, Japan, South Korea and Singapore using panel Augmented Mean Group (AMG) estimation techniques over the period 1975–2020. The results of the analysis show that renewable energy consumption, non-renewable energy consumption, employed labor force, and capital formation contribute significantly to long-run economic growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…Similarly, the interplay between CO 2 emissions and GDP, trade, urbanization, and industrialization highlights the reciprocal influence of economic growth and environmental impact. Such dynamics align with the findings of research conducted by Huang and Yi [132], Zhang et al [133], and Song et al [134], which also observed significant interdependencies between these variables. These interactions underscore the critical need for policy interventions that consider the mutual impact of environmental and economic variables.…”
Section: Dumitrescu-hurlin Panel Causality Testsupporting
confidence: 89%
“…Similarly, the interplay between CO 2 emissions and GDP, trade, urbanization, and industrialization highlights the reciprocal influence of economic growth and environmental impact. Such dynamics align with the findings of research conducted by Huang and Yi [132], Zhang et al [133], and Song et al [134], which also observed significant interdependencies between these variables. These interactions underscore the critical need for policy interventions that consider the mutual impact of environmental and economic variables.…”
Section: Dumitrescu-hurlin Panel Causality Testsupporting
confidence: 89%
“…This study further proves that this conclusion is still valid in the tourism industry of YRB. Long-term carbon emissions are greatly reduced by renewable energy use whereas they increase substantially by using energy that is not renewable 61 . Therefore, reducing the energy consumption intensity of TE or increasing the proportion of renewable energy are two effective ways to improve the quality of low-carbon tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on this subject is somewhat ambiguous. On the one hand, some studies, citing the World Bank in particular, maintain that economic growth is beneficial to the environment because an increase in per capita income is supposed to contribute to an improvement in environmental quality (Zhang et al. , 2023).…”
Section: Methodsmentioning
confidence: 99%
“…However, the literature on this subject is somewhat ambiguous. On the one hand, some studies, citing the World Bank in particular, maintain that economic growth is beneficial to the environment because an increase in per capita income is supposed to contribute to an improvement in environmental quality (Zhang et al, 2023). On the other hand, it is also suggested that economic growth can be detrimental to the environment, particularly due to the higher levels of production and consumption associated with increased economic growth (Naseem et al, 2023;Ayhan et al, 2023).…”
Section: Datamentioning
confidence: 99%